Hannibal - Harris, Thomas, 1940- (Delacorte Press, 1999)
A showdown between two psychopathic killers with a beautiful FBI agent caught in the middle. From his respirator, Mason Verger orders the capture of Hannibal Lecter, the man who put him there, and the bait is Clarice Starling with whom Lecter crossed swords in The Silence of the Lambs.